Learning Self-Reliance and Initiative of High School Students in Educational Modeling - E.V. Chudinova; V.Y. Zaitseva; D.I. Minkin (Moscow State University of Psychology and Education, 2024)
The task of the work is to present initiative and independent educational modeling as the highest possible achievement of high school students (15 -17 years old). The application of the "case study" within the framework of a multi-year genetic-modeling experiment made it possible to describe the precedents of educational modeling in high school, demonstrating the initiative and independence of students in modeling. An analysis was carried out of video recordings of 14 lessons on setting and solving one educational problem, the results of a focus group with 5 teachers and written work of 20 eleventh grade students. Due to prior learning based on the principles of learning activities, students of this age are able to invent and analyze modeling tools necessary to capture implicit subject relations, as well as to transform the model by holding the problem for the time necessary to solve it. In this case, the training model acquires the features of an exploratory model. It is shown that the model is not only a means of fixing subject relations for the classroom community, but also a way of expressing their understanding, i.e. a means of communication.